2022
DOI: 10.1088/1742-6596/2240/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Depth profiling of very thin HfO2/Al2O3 stacks by ellipsometry

Abstract: Ellipsometry (VASE and MAIE) with appropriate algorithms for experimental data interpretation was applied for quantitative characterization of thin Al2O3/HfO2 multilayers formed by atomic layer deposition (ALD) applicable to the fabrication of charge-trapping nonvolatile memories. A substantial benefit of the algorithms is the depth profiling of the stacks. In this work, the depth profiles were retrieved of the HfO2 constituent in very thin (Al2O3:HfO2) stacks embedded in thin Al2O3 surrounding layers. The pec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…used magnetron sputtering to grow gold films on two polymer film substrates and found that the growth mode was IG . However, there are relatively few studies on the ultrathin ALD-prepared metal oxide composite dielectric film. …”
Section: Introductionmentioning
confidence: 99%
“…used magnetron sputtering to grow gold films on two polymer film substrates and found that the growth mode was IG . However, there are relatively few studies on the ultrathin ALD-prepared metal oxide composite dielectric film. …”
Section: Introductionmentioning
confidence: 99%